Teaching practice in elementary school: reflections on the Supervised Internship III in the Geography course Licenciatura EaD of the Universidade Federal de Alagoas / Prática docente no ensino fundamental: reflexões sobre o Estágio Supervisionado III no curso de Geografia Licenciatura EaD da Universidade Federal de Alagoas - Lívia Thaysa Santos de Albuquerque Gama (Diversitas Journal, 2018)
This article summarizes reflections about the teaching practice, based on the experiences lived in the supervised stage, and will discuss the importance of the valuation of the teaching practice, as well as the relevance of the experiences of the trainees. However, it aims to list reflections about the teaching practice, based on the experiences lived in the supervised training, and it discusses about the importance of the valuation of the teaching practice, as well as the relevance of the experiences of students in the supervised training. The objectives of this work are related to the presentation of the specificities of the supervised training III in the Distance Learning License Degree Course / UAB / UFAL; it needs to highlight the experiences of students in the supervised training about observation and teaching practice; evidencing the importance of teaching practice in scholar routine. The development of this work was done through a bibliographical review, by the reading of some authors like: Borssoi (2008); Conde and Sá (2016); Corte and Lemke (2015); Pimenta and Lima (2005/2006); Pimenta (1995); Rodrigues (2015); exploratory technical visit, action research and experience report. Therefore, practical and theoretical methods were used.